(untitled) (Teacher’s World: Journal of Education and Research, 2024)
Action research has been found to be potential in solving classroom related problems in teachers’ own context and for bringing changes in classrooms making the classrooms more inclusive. Therefore, in a 5-country consortium project, while using a co-designed teachers’ professional development on Gender and Inclusive Pedagogy (GIP), action research was in-built as an important part for problem solving. In a four-tier training program, 95 teachers of the 20 experimental schools of Bangladesh were oriented with action research and gradually achieved necessary skills to practice action research in their classrooms. After each phase of trainings, teachers practiced action research as a tool to mitigate issues related to GIP practice. Both quantitative and qualitative data were obtained from three different sources- observation of the teacher training sessions related to action research, pre and posttests of the trainings, and reflective journals of the teachers. Findings reveal changes in teachers’ understanding, attitude and practice related to action research. Quantitative data shows that there are significant differences in teachers’ understanding related to action research between the pre and post tests in the last two tiers of the trainings. There is significant change in teachers’ ‘attitudes’ related to action research too between the pre and posttests in the third and final tiers of the trainings. Qualitative data also depicted the same gradual changes in teachers’ understanding of and attitude towards conducting action research. Lastly, 17 teachers (8 individually and 9 collaboratively) practiced action research in their classrooms to address different issue or challenges related to student participation and achievement regarding gender and inclusion aspects. The teachers reported reduced student absenteeism, increased student participation in group work, more participation of girls and special need children, more organized and student friendly classrooms. However, challenges remained in ensuring the participation of all students in a meaningful way ensuring quality learning which the teachers are trying to achieve in their next action research cycles. Teachers expressed their worries that they may not be able to continue the action research when the project period is over as there will be no support from the project team members. The study suggests creating groups among teachers in nearby localities who can share, help and collaborate in each other’s action research. Teacher’s World: Journal of Education and Research, 49 (2),15-36